Mating ability during chemically induced G1 arrest of cells of the yeast Saccharomyces cerevisiae. - Bedard, D P (1984)
Diploid formation by haploid cells of Saccharomyces cerevisiae was tested during and after treatment with chemical agents which bring about arrest at the cell cycle regulatory step "start." All compounds, except sinefungin, allowed efficient mating. During sinefungin treatment, zygote formation, but not karyogamy, was affected.